Chromosome microarray analysis should be offered to all invasive prenatal diagnostic testing following a normal rapid aneuploidy test result. Issue 4 (4th August 2020) - Rodriguez‐Revenga, Laia; Madrigal, Irene; Borrell, Antoni; Martinez, Josep M.; Sabria, Joan; Martin, Lourdes; Jimenez, Wladimiro; Mira, Aurea; Badenas, Celia; Milà, Montserrat
Abstract: Chromosomal microarray analysis (CMA) has now replaced karyotyping in the analysis of prenatal cases with a fetal structural anomaly, whereas in those pregnancies undergoing invasive prenatal diagnosis with a normal fetal ultrasound, conventional karyotyping is still performed. The aims of this study were to establish the diagnostic yield of CMA in prenatal diagnosis, and to provide new data that might contribute to reconsider current practices. We reviewed 2905 prenatal samples with a normal rapid aneuploidy detection test referred for evaluation by CMA testing. Our study revealed pathogenic and reported susceptibility copy number variants associated with syndromic disorders in 4.8% (n = 138/2905) of cases, being 2.8% (n = 81/2905) the estimated added diagnostic value of CMA over karyotyping. Clinically significant CMA abnormality was detected in 5.4% (107/1975) of the fetuses with ultrasound anomalies and in 1.4% (5/345) of those considered as low‐risk pregnancies. Our series shows that in prenatal samples, CMA increases 2‐fold the diagnostic yield achieved by conventional karyotyping. Abstract :